Features of the legal protection of information with restricted access of the State Aviation Service of Ukraine - Горбатюк, Яна Вадимівна (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2013)
In the article the author explores the concept of information with restricted access by analyzing the current legislation of Ukraine and the views of scientists and determines the characteristics of the legal protection of such information of the State Aviation Service of Ukraine.